Diseño e implementación de una red para el transporte de datos, voz e internet para conexión de nodos de fibra óptica de telconet Galápagos entre las islas santa cruz y San Cristóbal - Tapia Quintana, Cristóbal Omar (2011)
This professional project studies alternatives for establishing communication networks,including security systems and protection (lightning, grounding, etc.) data capacity transmission, licenses, etc. for various sectors of telecommunications among them military, civil and commercial sectors. The project has different stages which consist of a feasibility study, Interference and Loss Analysis, Infrastructure, Configuration and Implementation of equipment following the ISO 27001, information security standard for users located in the Galapagos Islands to make use of this infrastructure network to transport information including video, internet, voice over IP, etc. The implementation of the project was conducted following additional processes: land leases (hill Niño and Camote) for installation of infrastructure, transfer of technical staff to base stations in the Galapagos, network and cabling installation (3650 Cisco Catalys switch), Installation of electrical energy systems, installation of base stations, Legalization of frequencies to the regulator SNT, selection and installation of Motorola brand radio PTP600 for integration of the nodes to a hub located in San Cristobal Telconet Telepor. Final results were compiled and shipped to Telconet technical department. Transmission capacity between islands can reach 42Mbps.